The Quraysh Dialect: An Analysis of Its Eloquence and the Qur’an’s Exclusive Use of It - Dr. Athraa Hassan Radi Obaid Al-Azzawi (Journal of College of Education, 2025)
There is a conflict between different tongues about the leadership of linguistic eloquence and winning it among the Arabic dialects, which led to raising the most important question for students of the Arabic language concerned with its dialects: Is the Quraish dialect the most eloquent dialect? Was the Holy Quran revealed in it, or does it have features that make it occupy the leadership in linguistic eloquence? To address this most common debate among students of Quranic linguistic sciences, we stand on the concept of eloquence, which represents the desired summit in correct speech. The early scholars divided languages into varying degrees , some were given eloquence, and some were given ugliness. Among the dialects that have received great attention, both in ancient and modern times, is the Quraish dialect, due to the status and religious , social , economic , and political influence enjoyed by this tribe; and because it is the tribe of the Prophet of the Arab nation (may God bless him and his family and grant them peace) ; therefore, it has been the focus of attention of scholars. Researchers in this field have taken two approaches: the first : Its owners believe that linguistic eloquence lies in the dialect of Quraysh . The second: its owners went to the view that eloquence is not specific to Quraysh just as the revelation of the Qur’an was not specific to its language. After discussing the evidence presented on this topic, I concluded in this research that the classical language is the language based on selection from the characteristics of dialects, so that it is not dominated by one dialect, but rather a unified language that every Arab understands in the vast majority.